STRUKTUR KOMUNITAS MANGROVE DI KELURAHAN TAPUANG, KECAMATAN TAHUNA, KABUPATEN SANGIHE - Romario Pohos; Calvyn F.A Sondak; Antonius P Rumengan (Sam Ratulangi University, 2021)
The information about mangrove forest community structure in Tapuang village has never been reported. The location of the mangrove forest in this village is near to the settlements. Three line transects with 50 m distance were laid perpendicular to the shore. In each line transect, 5 quadrants (10 x 10 m2) were established. The data were analyzed using several parameters density, frequency, dominance, important index value and diversity. This study found 5 mangrove species namely Avicennia marina, Sonneratia alba, Sonneratia ovata, Rhizophora stylosa and Nypa fruticans. Avicennia marina was the most species found in each transects and had the highest density, frequency, and dominance values. The highest important value index (INP) was found in Avicennia marina in transect 2 with a INP value 183.80. Mangrove species diversity index for tree category in each transect was low (H'≤1) ranges from 0.99.Key Words: Tapuang Village, Mangrove, Community Structure